Evaluation of the role of remission status in a heterogeneous limited disease small-cell lung cancer patient cohort treated with definitive chemoradiotherapy - Manapov, Farkhad; Niyazi, Maximilian; Gerum, Sabine; Roengvoraphoj, Olarn; Eze, Chukwuka; Li, Minglun; Hildebrandt, Guido; Fietkau, Rainer; Klautke, Gunther; Belka, Claus (BMC Cancer, 2016)
The role of remission status in limited disease (LD) small-cell lung cancer (SCLC) patients treated with definitive chemoradiotherapy (CRT) remains to be finally clarified.Individual data from 184 patients treated with definitive CRT concurrently or sequentially were retrospectively reviewed. Kaplan-Meier analysis as well as univariate and multivariate Cox regression models were used to describe survival within patient subgroups defined by remission status.71 (39%) patients were treated in the concurrent, 113 (61%) in the sequential CRT mode. Prophylactic cranial irradiation (PCI) was applied in 71 (39%) patients. 37 (20%) patients developed local, while 89 (48%) distant recurrence. 58 (32%) patients developed metachronous brain metastases. Complete, partial remission and non-response (defined as stable and progressive disease) were documented in 65 (35%), 77 (42%), and 37 (20%) patients, respectively. In complete responders median overall survival was 21.8 months (95CI: 18.6 - 25) versus 14.9 (95% CI: 11.7 - 18.2) (p = 0.041, log-rank test) and 11.5 months (95% CI: 8.9 - 15.0) (p < 0.001, log-rank test) in partial and non-responders, respectively. The same effect was documented for the time to progression and distant metastasis-free survival. In the multivariate analysis achievement of complete remission as a variable shows a trend for the prolonged time to progression (p = 0.1, HR 1.48) and distant metastasis-free survival (p = 0.06, HR 1.63) compared to partial responders and was highly significant compared to non-responders.In this treated heterogeneous LD SCLC patient cohort complete remission was associated with longer time to progression, distant metastasis-free and overall survival compared to the non- and especially partial responders.
EVALuna2:18335